2008
DOI: 10.1017/s0022215108002156
|View full text |Cite
|
Sign up to set email alerts
|

Screening for hearing loss and middle-ear effusion in school-age children, using transient evoked otoacoustic emissions: a feasibility study

Abstract: These results strongly suggest the potential usefulness of otoacoustic emission testing in screening school-age children for hearing loss. Further studies, taking into account cost-effectiveness issues, are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2012
2012
2106
2106

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 16 publications
(19 reference statements)
1
32
0
6
Order By: Relevance
“…Briefly, 10 primary studies were included in this update. 17,[22][23][24][25][26][27][28][29][30] One was published before 2005 24 but was included here as it had been missed by the original 2007 HTA report. 12 The other nine studies were published in the period 2005-2014.…”
Section: Search Results and Selection Of Studiesmentioning
confidence: 99%
“…Briefly, 10 primary studies were included in this update. 17,[22][23][24][25][26][27][28][29][30] One was published before 2005 24 but was included here as it had been missed by the original 2007 HTA report. 12 The other nine studies were published in the period 2005-2014.…”
Section: Search Results and Selection Of Studiesmentioning
confidence: 99%
“…15 While comparing the type of tympanogram in referred population B type was most common found followed by C type and As type. A study on Otoacoustic emissions in a screening on school-age children reported that 20% children failed in both ears and 32% in at least one ear 16 . In the present study the refer rate was reported separately for the right (29.1%) and the left (33.1%) The difference in the two studies may be credited to the factors like awareness among the population, difference of geographical areas and availability of medical facilities.…”
Section: Whomentioning
confidence: 99%
“…Penelitian Georgalas dkk., 11 Grundfast dkk., 12 dan WHO 2 pada anak sekolah dasar, OME merupakan penyebab gangguan dengar yang paling banyak ditemukan. Pada penelitian diagnosis OME juga paling banyak ditemukan (Tabel 1).…”
Section: Pembahasanunclassified
“…Hasil ini tidak terlalu jauh berbeda dengan penelitian skrining pendengaran dan otitis media pada anak sekolah yang dilakukan oleh Georgalas dkk., 11 yaitu didapatkan perbandingan laki-laki dengan perempuan 1,08:1 serta perbandingan penelitian Ratunanda 8 pada anak kelas satu tersangka OME di beberapa sekolah dasar kota Bandung dengan perbandingan 1,5:1.…”
Section: Pembahasanunclassified